Relationship between the level of physical activity and attention of high school students in a public school in the interior of Minas Gerais (Research, Society and Development, 2021)
This study aimed to verify and compare the level of attention and the level of physical activity in high school students from a school in Piraúba-MG. For this, adolescents of both sexes aged 15 to 17 years were evaluated. As assessment instruments, two tests were used. The first test applied was the International Physical Activity Questionnaire (IPAQ- short version), which seeks to estimate the level of physical activity of the individuals evaluated. Then, the Attention Cancellation Test (CAT) was used, consisting of activities to cancel pictures in three stages and different levels (TAC1, TAC2, TAC3), being used to estimate the level of attention, both tests were applied from in person. The results indicated a better performance in the attention test of students who were classified as Active, mainly in the first part of the test (TAC1), with a better time and a lower percentage of errors. Thus, it is concluded that active adolescents obtained a better result in a specific part of the test (TAC1), with regard to the level of selective attention.